Posisi Ideologi Maskulinitas Fatherhood Dalam Film Bernuansa Islami “Hafalan Shalat Delisa” - Himawan, Hilmi; Rahardjo, Turnomo; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Traditional, patriarchal masculinity has reinforced rigid, authoritarian male roles, often leading to emotional distance between fathers and their children. The advent of the information age has ushered in a new ideology of masculinity known as 'fatherhood', which emphasizes active involvement in family life and the cultivation of deeper emotional connections. This study examines the representation of fatherhood masculinity in the film